(untitled) - Sheerin, Susan (Oxford, 1990)
The book gives a region-by-region account of life in the United Kingdom. The wide variety of topics includes London, TV and Radio, Liverpool and the Beatles, Stratofrd and Shakespeare, Northern Ireland. Interesting information combines with opportunities for lively discussion, and students are provided with comprenhension questions and language practice exercises.
Keywords: English language; Study and teaching